(untitled) (مجلة المنصور, 2022)
Quantum computation is a new field bridging many disciplines, including theoretical physics, functional analysis and group theory, electrical engineering, computer science, and quantum cryptography. The goal of this paper is to explore the base of quantum computation that serves to build up a secure algorithm for keys in the unsecured communication channel between two hosts (computers) by applying quantum key exchange algorithm which has highly guarantee protecting toward the computational complexity because the quantum key exchange algorithm is more complex in computation than the classical key exchange algorithm if it perform in classical computer. Also, this algorithm (key exchange algorithm) provides the ability to perform in quantum computer if will be available in future.